Quantifying the coating yield by modeling heat and mass transfer in a Wurster fluidized bed coater - Madlmeir, S.; Forgber, T.; Trogrlic, M.; Jajcevic, D.; Kape, A.; Contreras, L.; Carmody, A.; Liu, P.; Davies, C.; Sarkar, A.; Khinast, J.G. (Chemical engineering science, 2022)
[Display omitted] •Full-physics CFD-DEM simulation of a pharmaceutical coating process.•Models for multicomponent spray evaporation and spray drying.•Possible reduction of coating losses from 28.2% to 6.1%•Evaluation of process robustness for various parameters. During the coating process of medicines, premature drying of the spray droplets may cause losses, as the droplets do not stick to the product. This work addresses two mechanisms that are central to predicting the heat and mass transfer in coating processes: (i) the evaporation of multicomponent spray liquids and (ii) the quantification of losses due to spray drying. We modeled a Wurster coating process via CFD-DEM simulation and validated the results based on temperature and coating-yield measurements obtained in lab-scale experiments. We assessed the effects of the inlet air flow rate, inlet air temperature and spray rate on the drying performance in a set of virtual experiments. Our calculations show that spray-drying losses can be reduced from 28.2% to 6.1% by selecting appropriate values of the input parameters. Implementing these results in a real coating system will maximize the coating yield and can reduce the process time by up to 75%.